STUDI ANALISIS PEMERINTAHAN YANG BAIK DAN BERSIH DI DESA GARANTA KABUPATEN BULUKUMBA PERSPEKTIF SIYASAH SYAR’IYYAH - Budiasri, Budiasri; Basri, Halimah; Asmar, Abdul Rais (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2022)
One of the goals of the state is to provide welfare for the people through the administration of a state that is free from corruption, collusion and nepotism. Corruption is a crime with a crime rate classified as serious crime because this action is detrimental to the state, corruption itself is an activity where the perpetrator takes state funds for personal gain. To run a government that is clean from KKN at the village government level, it is necessary to pay attention to Law no. 28 of 1999 concerning the Implementation of a Clean and Free State from Corruption, Collusion and Nepotism and also Law no. 6 of 2014 concerning Village Government. The village government as the part that is most closely related to the community, the village government has an important role in aspects of national development in order to create a prosperous, just and prosperous society in accordance with the constitution of the Republic of Indonesia. Regarding the concept of clean government in Garanta Village, Kec. Ujungloe Kab. Bulukumba, the village government in this case as the village head of Garanta explained that the concept of clean government is to prioritize the principles of transparency and accountability in order to inform the public of the activities and developments that are planned. To encourage good government implementation, the village government also seeks to develop its village community to be more advanced and increase human resources in the Garanta village. The intended guidance is community development in the health sector and in other fields there is also youth development. Regarding the Garanta Village development plan that has been discussed with the village community, namely by building in each hamlet a Qur'an Education Park, building a Tugu or Village Triangle Park, as well as improving drainage and irrigation. The researcher was involved in assisting the process of implementing the selection of new village officials, taking into account the entire selection process. It can be concluded that the entire flow of government in Garanta Village has been free from Corruption, Collusion and Nepotism, this is based on the government that prioritizes transparency in carrying out all activities and development, as well as involving the community to actively participate in overseeing village government activities. Seen from the perspective of Siyasah Syar'iyyah, the government of Garanta Village has carried out the mandate well which refers to the Qur'an and Hadis.